Keadilan Dalam Penyelesaian Perkara Pidana Secara Adat Di Desa Papring Kalipuro Banyuwangi - Arie Ramadhani; Desi Yunita Putri; Roudhotul Jannah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to compile a codification of customary law in the village of Papring where in the future it will also be composed of changes from time to time so that it remains sustainable and becomes a reference for resolving criminal cases that fulfills a sense of justice for the Papring residents themselves. This research approach uses a normative approach and an empirical approach. This normative approach is carried out within the framework of understanding the material law of customary criminal law which is spread across various research results, models for resolving customary criminal cases in Papring village, doctrine and comparisons of other customary criminal laws in Indonesia. Meanwhile, an empirical approach was used to find out the extent of the use of customary criminal law in Papring village and the existence of new rules that have developed and apply both materially and formally. The results of this research are: Criminal cases of entering someone else's house without permission and fraud cases will be subject to fines and compensation from the victim to the perpetrator. This settlement contains the principle of a win-win solution and achieves the highest justice and justice is carried out quickly, simply and at low cost.